Time-series forecasting analysis on dental treatment need of first-visit patients at IIUM Dental Outpatient Clinic (Periodontal and Conservative Department) for the year 2017 and 2018 - Muhammad Radhi, Nur Aishah; Musa, Syazalina; Ismail, Azlini; Abllah, Zurainie (2018)
Introduction: Periodontal and conservative treatment need among first-visit patients at IIUM Dental Outpatient Clinic was high. This study aimed to identify the major periodontal and conservative treatment need, to analyse previous trend and to forecast future need. Materials & Methods: Ethical approval (IREC762) was obtained from IIUM Ethics Committee. List of first-visit patients who attended this clinic from 1st January 2014 to 31st December 2016 was retrieved to assess for patient’s age, gender and residential areas. Patients with incomplete data were excluded. Treatment need was determined by dental-officer-in-charge. Association between age, gender and residential-area with the type of major treatment need was analysed using Chi-square test in SPSS Version 20. Time-series forecasting analysis was conducted using Minitab Version 17. Results: Majority of our samples were females (62.0%), aged 20 to 34 year-old (54.5%), and from urban areas in Kuantan (42.4%). Major treatment need for periodontal and conservative care was scaling-polishing (65.0%) and filling (74.1%), respectively. Age (P<0.001) and residential-area (P<0.001) have significant associations with the type of major treatment need. The need for single-treatment of scaling-polishing or filling or the need for both treatments was highest in the age group of 20 to 34 year-old and had predilection for urban residents of Kuantan. Three-year weekly trend (2014-2016) for scaling-polishing was plateau and for filling was minutely declined. This study forecasts that there will be 741 and 855 first-visit patients/year in 2017 and 2018 that requires scaling-polishing and filling, respectively. Conclusions: The need for scaling-polishing and filling in this sample population in 2017 and 2018 will remain high, as seen in the previous three years.